The slow, the quick and the dead: environment, politics and temporality in the Henan famine, 1942-43 - Baker, M (Australian National University Press, 2018)
This article argues that famines have rapid as well as slow temporalities. Using newspapers, contemporary eyewitness accounts and subsequent memoirs, it uncovers the mixed temporalities of causation and experience in the 1942–43 famine in Henan Province, north-central China. It begins by exploring how the slow elements of famine played out in Henan: endemic poverty and malnutrition, years of war in the province, and the drawn-out experience of drought and starvation in 1942–43. More importantly, though, it then demonstrates that it was rapid processes that tipped much of Henan into what one observer called a ‘blitz famine’: hailstorms, price spikes and the violence of military requisitioning. The experience of famine, too, had fast temporalities, including snap decisions about flight, individual or collective acts of violence, and the sudden bodily collapse that often followed the slow process of starvation. But if all famines have mixed temporalities, this article closes by showing that these elements of time are not politically neutral. Comparing 1942–43 with Henan’s other major twentieth-century famines (1920–21, 1928–30 and 1958–61), I argue that the growing role of the state in causing famine led to faster temporalities of disaster.